Study of prevalence of Sexual dysfunction in Alcohol Dependant individuals: A cross sectional study - Pavan Kumar K1 , Apurva Chada2 , Ravinder Anaveni3 , Sinjoni Roy4 (Perspectives In Medical Research, 2017)
Background: The chances of developing sexual dysfunctions appear to increase with increasing years of alcohol consumed. Various explanations have been offered for sexual dysfunction in alcoholic patients. The prevalence of sexual dysfunction causes significant distress and affects the relationship of a couple. Aims: Our study was an attempt to find out the presence of sexual dysfunction in alcohol dependant individuals and correlate with severity of Alcohol Dependence Materials & Methods: Sixty male in-patients who were diagnosed as alcohol dependence syndrome according to ICD10 were assessed for severity of dependence using Severity Of Alcohol Dependence Questionnaire (SADQ) and Assessment of sexual disorders was done using Arizona Sexual Experiences Scale (ASEX). Relationship between the severity of alcohol dependence and presence of sexual disorder is analyzed using chi square test and spearman’s correlation coefficient test using SPSS software. Results: Sixty percent of our patients with alcohol dependence had sexual dysfunction. The level of alcohol dependence has significant association with the sexual dysfunction. Conclusion: Sexual dysfunction and alcohol dependence are proportionately related. Clinicians need to assess sexual dysfunction in all patients presenting with Alcohol Dependence